Latihan Otot Progresif Untuk Keletihan Pada Penderita Diabetes Melitus - Antoni, Adi; Simamora, Febrina Angraini (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Diabetes mellitus is a degenerative disease whose number is increasing every year. This disease must be experienced for life and can cause various problems including fatigue. Puskesmas Labuhan Rasoki is one of the Aufa Royhan Health School areas who have diabetes sufferers. The purpose of this service is to help people who suffer from diabetes manage the fatigue they experience. The method used was counseling to 28 diabetics by providing progressive muscle relaxation exercises. In addition, demonstrations and redemonstrations related to this exercise were also provided. After being given a demonstration of progressive muscle relaxation, the participants were very enthusiastic and happy because there are cost-effective alternative methods for managing fatigue in diabetics.